Air quality (AQ) identification by innovative trend diagram and AQ index combinations in Istanbul megacity - Güçlü, Yavuz Selim; Dabanlı, İsmail; Şişman, Eyüp; Şen, Zekâi (Turkish National Committee for Air Pollution and Control (TUNCAP), 2019)
Istanbul is one of the megacities with population over 14 million, where the most intensive economic and social human activities take place in Turkey with unprecedented energy consumption and extravagant life style. These activities cause air pollutant emissions and concentrations increases under the additional effects of greenhouse gasses and waste heat with their impacts on ecosystems, climate change and air quality. In order to control and improve the air quality at different quarters of Istanbul City, various air pollutants are monitored for effective combat For this purpose, time series records of the pollutants (particulate matter <10 mu m in diameter such as dust, pollen, mold, etc. (PM10), carbon monoxide (CO), sulfur dioxide (SO2) and nitrogen dioxide (NO2)) are subjected to innovative trend diagram (ITD) analysis coupled with the air quality index (AQI) classification according to the US Environmental Protection Agency health status. Linguistic AQI classes are considered for pollutant levels with linguistic trend interpretations through the ITD diagram. The combination of ITD and AQI provides opportunity to detect trends at each class. The application of the methodology is presented for Esenler and Besiktas stations on the European, and Kadikoy and Umraniye stations on the Asian sides of Istanbul City.
WOS: 000454999000010
Keywords: Air Pollutants; Air Quality; 1:1 (45 Degrees) Straight-Line; Trend Analysis; Istanbul